Pengetahuan Ekspresi Karya Musik - Wisnu Mintargo (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2008)
Expression in music is a movement in feeling that is formed through the media of sound. This means that music comes out of the soulâ€™s creator through hearing, experienxed and felt by a human being who gave his whole soul and feelings to enjoy the music. A form of musical statement comes from the nature of thought, imagination and the artis â€˜sftelings are influenced by the power outside of him as inspiration. Either than that, the creative process is always in line with music knowledgeÂ